Refrigeration and cryopreservation of platelets differentially affect platelet metabolism and function: a comparison with conventional platelet storage conditions. Issue 7 (9th May 2016) - Johnson, Lacey; Tan, Shereen; Wood, Ben; Davis, April; Marks, Denese C.
Abstract : BACKGROUND: Alternatives to room temperature storage of platelets (PLTs) may be beneficial to extend the limited shelf life and support transfusion logistics in rural and military areas. The aim of this study was to assess the morphologic, metabolic, and functional aspects of PLTs stored at room temperature or in refrigerated conditions or cryopreserved. STUDY DESIGN AND METHODS: A three‐arm pool‐and‐split study was carried out using buffy coat–derived PLTs stored in 30% plasma/70% SSP+. The three matched treatment arms were room temperature stored (20‐24°C), cold‐stored (2‐6°C), and cryopreserved (−80°C with dimethyl sulfoxide). Liquid‐stored PLTs were tested over a 21‐day period, while cryopreserved PLTs were examined immediately after thawing and after 6 and 24 hours of storage at room temperature. RESULTS: Cold‐stored and cryopreserved PLTs underwent a significant shape change, although the cryopreserved PLTs appeared to recover from this during subsequent storage. Glycolytic metabolism was reduced in cold‐stored PLTs, but accelerated in cryopreserved PLTs, while oxidative phosphorylation was negatively affected by both storage conditions. PLT aggregation was potentiated by cold storage and diminished by cryopreservation in comparison to room temperature–stored PLTs. Cold storage and cryopreservation resulted in faster clot formation (R‐time; thromboelastography), which was associated with an increase in microparticles. CONCLUSION: Cold storage and cryopreservation of PLTs led to morphologic and metabolic changes. However, storage under these conditions appears to maintain or even enhance certain aspects of in vitro PLT function.